Colonialism, society and reforms in Malaya: a comparative evaluation of Shaykh Tahir Jalaluddin and Syed Shaykh Ahmad Al-Hady - Zakariya, Hafiz (IIUM Press, International islamic University Malaysia, 2017)
Early twentieth-century Malaya witnessed the emergence of Islamic reformist movement. Inspired by ‘Abduh, Malay reformists, epitomized by Tahir Jalaluddin and Ahmad al-Hady, discontented with the socio-economic and political conditions of the Malays, criticised the Malay ruling elites and called for reform of their society. While the former worked within the framework of formal Islamic scholarship as an ‘ālim, the latter primarily operated as a public intellectual who spoke to a broad audience, at least in the urban centres of the Straits Settlements. This study compares their careers and ideas regarding colonialism and their remedies to address the socio-economic conditions of Malay society and the intellectual crisis of the Muslims.